EUROPEAN UNION IN COMBATING HUMAN TRAFFICING - Ketevan Kukhianidze (European Scientific Journal, ESJ, 2012)
Every day several thousand of people are trafficked in different countries in searching better life. Modern day slavery,trafficking in human beings, presents a grave human rights violation. This is the problem, which covers social, political, anddemographic aspects, as well as gender and ethnic stratification, transnational organized crime and human rights abuses, andthe facility of states and supranational institutions effectively to deal with those issues. It seems that one of the core causes oftrafficking in persons is poverty related to the inequalities between economically developed countries and less developedones. This main factor pushes people to migrate to different countries, as they have no other options to feed their families. Intandem, pull factors such as European demographic problems ensure continuing demand. Consequently, individual nations’efforts cannot succeed unless global efforts are harmonized and these push and pull factors are addressed. This paper presentsthe positive and negative aspects of European legal documents in combating trafficking in human beings, where we canclearly see the minuses which need to be overcome.